L'enseignement d'une élite? a (re)invenção das tradições na Academia Militar Paulista (1931-1944) - Loureiro, Samuel Robes (2012)
This dissertation studies the history of the Academia de Polícia Militar do Barro Branco (APMBB) through the perspective of the traditions implemented at the school during the decade of 1930, especially the traditions of the historical uniform and of the small sword, that composed a project of modernization of the military teaching of São Paulo driven by officials of the National Army that acted as intervenors at Força Pública do Estado de São Paulo (FPESP) during the Vargas Era (1930-1945). The research search to contribute with the studies on the military teaching in Brazil, mainly the study of the teaching in the Military Police. Looking for alternatives to the referential of the official history and to the Althusser structuralism, a researchers referential is used, such as Thompson (1981) and Hobsbawn (1989, 1997), especially about the invention of the traditions. During the research, it is evidenced that the traditions invented for the Centro de Instrução Militar (CIM) of FPESP during the period in that Colonel Milton de Freitas Almeida commanded the institution, in other words, between 1935 and 1938, culminated with the inauguration of the new facilities of CIM in Invernada do Barro Branco, in 1944. Therefore, it is made a compared study about the evolution of the teaching in the schools of formation of the Army between 1810 and 1944 and of FPESP between 1831 and 1944, to verify which were the influences and the objectives of these alterations in the military teaching of São Paulo. With that, it is demonstrated that the creation of these traditions followed the model implemented by Colonel José Pessoa in Escola Militar do Realengo (EMR) between 1931 and 1934, when the traditions of the historical uniform, of the small sword and of the Body of Cadets were invented to the formation school of officials of the Army. This reform in the school culture of EMR had the objective of, through the creation of the feeling of belonging to an aristocratic group with its own ceremonial and group of traditions, inculcate in the students a such discipline that moved them away from the pernicious politics, that had led officials generations to the rebelliousness of the Tenente revolts. The research proves that the José Pessoa Reform was copied in CIM of FPESP during the Freitas Almeida Reform, with the same objective of disciplining the officials of FPESP. However, in the case of the Freitas Almeida Reform, there was another underlying objective: to reformulate the culture of FPESP so that the members of the corporation accepted the condition of being transformed in reserve force of the Army